Evaluasi Pasca Diklat Tim Pendamping Keluarga dalam Rangka Percepatan Penurunan Stunting - Susanti, Annastasia Nika; Banuwa, Anisa Kuswandari (Penerbit Goodwood, 2025)
Purpose: This study aims to determine the results of the post-training evaluation (TPK orientation). Research methodology: The research method used in this study is a quantitative method. The data used are primary data obtained from the results of questionnaires distributed to 152 respondents from 7 districts/cities in Lampung Province. Results: Data analysis was carried out descriptively using visualization in the form of diagrams and tables. From the results of the analysis, it is known that the knowledge of the respondents is quite good but still needs further exploration, especially on the material for using the Elsimil application. In addition, the implementation of the TPK orientation activities was in accordance with the planned TOR (Term of Reference). Meanwhile, from the follow-up aspect, the involvement of districts/cities in providing guidance to TPK is still not evenly distributed because several districts/cities have not carried out further guidance for TPK. Conclusion: Based on the descriptive analysis, respondents’ knowledge is generally good but still requires further improvement, particularly in the use of the Elsimil application. The implementation of the 2021 TPK Orientation aligns with the TOR provided by BKKBN Lampung Province, although follow-up guidance by districts remains uneven. Limitations: For further research, it is hoped that researchers can take a larger number of samples from 15 districts/ cities that the evaluation results will be more representative for future improvements. Contribution: The results of this study can be a reference for BKKBN Lampung Province in conducting appropriate training especially in accelerating stunting reduction through TPK orientation.